2011
DOI: 10.1007/s10853-011-5543-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on process-induced morphological characteristics of macro- and microstructures in laser consolidated alloys

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Experimental studies on process-induced morphological characteristics of macro-and microstructures in laser consolidated alloys Chen, J.; Xue, L.; Wang, S.-H. NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21271454&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21271454&lang=fr READ THESE TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…These columnar grains have been observed in both SLM powder-bed [13] and blown-powder laser fabricated [14][15][16][17][18] materials. The results presented by Liu et al [15] are of particular interest as they show not only the columnar grains within the blown-powder laser fabricated material, but also fine grained regions formed due to the scan spacing.…”
Section: Grain Structure In Laser Fabricated Materialsmentioning
confidence: 85%
“…These columnar grains have been observed in both SLM powder-bed [13] and blown-powder laser fabricated [14][15][16][17][18] materials. The results presented by Liu et al [15] are of particular interest as they show not only the columnar grains within the blown-powder laser fabricated material, but also fine grained regions formed due to the scan spacing.…”
Section: Grain Structure In Laser Fabricated Materialsmentioning
confidence: 85%
“…A variety of LMD machines and laser systems are being used for the fabrication of metals and alloys including Ti-6Al-4V, such as LEMS TM Nd:YAG, Trumpf HLD 3504 Yb:YAG and IPG with Yb fibre laser [67][68][69][70][71][72][73][74][75][76][77][78]. Figure 4 and Table 5 present the general working principle, working conditions and key machine/processing parameters.…”
Section: Laser Metal Deposition (Lmd)mentioning
confidence: 99%
“…The issue of cracking is typically not addressed as much of this research deals with the more easily processed materials of Inconel 718 [21][22][23] and Inconel 738 [23][24][25], which either have a lower γ′ fraction or the slower precipitating γ′′ phase, thus reducing the susceptibility for weld cracking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the grain structure, the γ′ structure of laser deposited material has been shown to be quite different to that of a conventionally formed material. Several authors have reported a limited precipitation of the γ′ phase due to the rapid cooling of the material following deposition [23,25,27] and as such will influence the heat treatment required to idealise the microstructure for functional use. The presence of residual stress in laser fabricated Ni-based superalloys poses a significant area of interest with studies being carried out into measurement [21,31] and modeling [32].…”
Section: Introductionmentioning
confidence: 99%